PERAN MEDIASI PROFITABILITAS PADA DAMPAK IMPLEMENTASI PSAK 71 TERHADAP TAX AVOIDANCE - Puspa Kirana Harwinanda; Anastasia Filliana Ismawati; Cliff Kohardinata (Jurnal Aplikasi Akuntansi, 2023)
PSAK 71 emerged as an adaptation of IFRS, which was present in response to demands against the International Accounting Standards Board (IASB) to update financial risk calculations. PSAK 71 encourages corporate conservatism so that in managing financial assets, it can estimate the risk of loss as soon as possible. This study aims to determine whether profitability can mediate the effect of PSAK 71 on tax avoidance activities in Indonesian banking from 2017-2021. The panel data model with path analysis is used to perform statistical data processing to achieve this study's objectives. The results of processing statistical data on 45 sample companies show that with the Sobel test, profitability can fully mediate the effect of PSAK 71 on tax evasion, as seen from the acquisition of a z value of 2.129, above an alpha of 1.96. This shows that the presence of PSAK 71 in Indonesia provides good news for stakeholders because it can reduce the level of tax avoidance activities that are detrimental to the government budget and mislead financial report users in making decisions.